The Correlation between Hearing Loss and the Quality of Life of Workers Exposed to the Noise in the Textile Industry - Sumardiyono, Sumardiyono; Wijayanti, Reni; Hartono, Hartono; Probandari, Ari (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Noise is a stressor for hearing loss among workers. Unfortunately, hearing loss also affect workerÃ¢â‚¬â„¢s quality of life. This study aimed to investigate the correlation between hearing loss and quality of life among workers in textile industry. The study design was a cross-sectional survey.Ã‚Â The study population were 200 workers exposed to the noisy textile industry. The data were analyzed using Spearman's rank correlation coefficient. The findings showed a significant relationship between hearing loss and the quality of life of the workers (rs=-0.698; p=0.000). The dimensions of quality of life associated with hearing loss were the Physical Functioning (rs=-0.493; p=0.000), Role-Physical (rs=-0.501; p=0.000), Bodily Pain (rs=-0.516; p=0.000), General Health (rs=-0.497; p=0.000), Vitality (rs=-0.527; p=0.000), Social Functioning (rs=-0.521; p=0.000), Role-Emotional (rs=-0.521; p=0.000), and Mental Health (rs=-0.517; p=0.000). This study concludes that hearing loss decreases the quality of life among workers exposed to the noise of the textile industry.